FACTORS INFLUENCING THE ADOPTION OF AGRICULTURAL INSURANCE AMONG CROP FARMERS AS CLIMATE CHANGE ADAPTATION STRATEGY IN BORNO STATE, NIGERIA - Baba, A. M.; Abdullahi, S.; Garba, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study examined the adoption of agricultural insurance among crop farmers as climate change adaptation strategy in Borno State, Nigeria. Multistage stage sampling technique was used in selecting 270 respondents for the study. Data were collected using structured questionnaire and analysed using descriptive and inferential statistics. The results reveal that the majority of respondents were between 36 and 49 years old, with a mean age of 37 years. Majority (60.7% and 80%) of the respondents were male and married. The mean household size, farm size, farming experience, and income of the respondents were 7 persons, 2 hectares, 7 years and ₦261,300, respectively. A reasonable proportion (37.8%) of the respondents had secondary education with majority (74.8%) having no access to credit. Most (83.0%) of the respondents in the study area had access to extension services. Majority (69.3%) of the respondents were aware of agricultural insurance. with a mean of 2 years of awareness. Half (50.0%) of the respondents sourced information on agricultural insurance from cooperatives. The major type of insurance adopted by the respondents were theft (20.0%), diseases (17.0%), and pest outbreaks (15.9%). The factors influencing the adoption of agricultural insurance in the study area were age (P < 0.01), educational level (P < 0.05) and access to extension services (P < 0.01). The major constraints to the adoption of agricultural insurance in the study area include high premium costs (71.1%) and inadequate awareness (70.0%) to mention few. The study concludes that age, education level and access to extension services were the factors influencing adoption of insurance as climate change adaptation strategy in the study area. The study recommends that the government and non-governmental extension services should embark on sensitization campaign to raise the awareness crop farmers on the importance of insurance and effort should be made by the concern stakeholders to subsidize the premium in order encourage patronage.